The new accounting manual a guide to the documentation process - Murtuza, Athar (John Wiley & Sons, 1995)
Shows how to produce an accounting procedures manual using sources other than traditional bookkeeping procedures such as activity-based costing, work simplification rules, process reengineering, information systems analysis and operational auditing.